Penatalaksanaan Fisioterapi Berbasis Sensomotor pada Anak dengan ADHD: Studi Kasus di Klinik PNTC Colomadu Jawa Tengah - Eva Widiyaningsih; Amalia Solichati Rizqi; Yudha Wahyu Putra (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder characterized by difficulties in sustaining attention, hyperactivity, impulsivity, and sensory regulation problems that may affect children’s daily activities. These conditions can influence motor function, behavior, social interaction, and participation in routine activities. This study aimed to describe sensorimotor-based physiotherapy management and clinical responses in a child with ADHD. A case study method was used, involving six physiotherapy intervention sessions conducted at PNTC Colomadu Clinic from January 9 to January 20, 2026. The interventions included Neuro Senso Motor Reflex Integration, brain gym, blocking, play-based functional exercises, and general massage. Evaluations were performed using the Pediatric Balance Scale (PBS), Pediatric Evaluation of Disability Inventory (PEDI), and Sensory Profile. The results showed no measurable objective changes in PBS, PEDI, and Sensory Profile scores from T1 to T6. The child demonstrated relatively good basic balance, particularly static balance, but still had limitations in dynamic balance requiring concentration and motor control. Observationally, the child appeared calmer, more cooperative, and better able to follow simple instructions. Longer and consistent interventions are needed to achieve meaningful objective outcomes.